The Difference of Social Science Achievement Using Project-Based Learning Outdoor Study with Conventional Study of Junior High School Students - Ratna Danarti (Universitas Negeri Malang, 2015)
Perbedaan Hasil Belajar IPS Model Project-Based Learning Berbasis Outdoor Study dengan Konvensional Siswa SMP Abstract: The aim of this research is to know the difference of students learning outcomes before and after the implementation of project based learning (PBL) models based on the outdoor study also to know the difference of students learning outcomes between PBL models based on the out-door study and conventional model in the seventh graders. This research practices experimental qu-asi research guidelines by using pretest-posttest nonequivalent control group design technique. Subjects of this research are VII A class and VII B of SMP Negeri 2 Ponorogo. The research instruments used are syllabus, learning plan procedure, and the outcomes of learning test. The research shows that PBL models based on the outdoor  study runs well as well as the syntaxes, in which students' responds are good. There are differences of social science learning outcomes before and after PBL models based on the outdoor study. There are differences between social studies learning outcomes using PBL models based on the outdoor study and conventional model. PBL models based on the outdoor study succeeds well when learning objectives are oriented on affective (attitudes) and psy-comotor (skills). On the other hand, conventional model is better for learning objectives wich are ori-ented on cognitive aspects (knowledge). Key Words: social studies learning outcomes, project based learning models based on the outdoor  study, conventional model Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar siswa sebelum dan se-sudah penerapan model Project-Based Learning (PBL) berbasis Outdoor Study serta mengetahui perbedaan hasil belajar siswa antara kelas model PBL berbasis Outdoor Study dengan konvensional pada siswa kelas VII. Penelitian ini menggunakan rancangan penelitian kuasi eksperimen dengan menggunakan teknik pretes-posttest nonequivalent control group design. Subjek penelitian adalah kelas VII A dan VII B SMP Negeri 2 Ponorogo. Instrumen penelitian yang digunakan berupa silabus, RPP, dan tes hasil belajar. Hasil penelitian menunjukkan bahwa pembelajaran model PBL berbasis Outdoor Study dapat berjalan dengan sangat baik sesuai dengan sintak-sintaknya dan respon siswa menunjukkan hasil yang sangat baik juga. Terdapat perbedaan hasil belajar IPS sebelum dan sesudah pembelajaran model PBL berbasis Outdoor Study. Terdapat perbedaan hasil belajar IPS model PBL berbasis Outdoor Study dengan model konvensional. Model PBL berbasis Outdoor Study berhasil dengan baik ketika tujuan pembelajaran berorientasi pada ranah afektif (sikap) dan psikomotor (kete-rampilan). Sedangkan untuk tujuan pembelajaran berorientasi pada ranah kognitif (pengetahuan), model konvensional lebih baik. Kata kunci: hasil belajar IPS, model project-based learning berbasis outdoor study, model konvensional